An approach of Fuzzy AHP to analyze the factors of domestic violence among women in malaysia / Nurain Syahirah Mahusin and Norpah Mahat - Mahusin, Nurain Syahirah; Mahat, Norpah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The number of women who be victims of domestic violence is increasing. Hence, the responsible party must take appropriate action to prevent this problem expand. This study’s goals are to rank the factor of domestic violence among woman in Malaysia and identify the most important sub-factor that influence domestic violence among women in Malaysia happened. Fuzzy Analytic Hierarchy Process method had been chosen to rank the factors of domestic violence among women in Malaysia: hot-tempered partner, jealousy, and substance abuse. This project will focus on the factors of domestic violence in Malaysia. This study used data collected from counseling unit of UiTM Perlis, checking for common factors for this study.